(3GdJfXje h CSGdjH GdYed (B/s - (3CHh TjNI, fGOQ CMeOs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2011)
(3fXQjGJ GdGOGQI h GdJWhjQ GdGOGQj, GdJWhQ GdGOGQj Hjf GdacQ h GdeeGQSI aj GdOhd GdYQHjI, eONd Gdi GdJfXje h GdCSGdjH, GdJfXje chXjaI EOGQjI, CHYGO Gdgjcd GdJfXjej h eMOOGJg h feGPL Gdgjcd GdJfXjej, GdNQGFW GdJfXjejI h GdfeGPL, JUeje GdecJH h JHSjW ELQGAGJ GdYed h CNjQG cJGHI GdJbGQjQs
Keywords: (3GdEOGQI GdYGeIs; (3GdYed hGdYeGd(B- (3JfXje hEOGQIs